'A disease that makes criminals': encephalitis lethargica (EL) in children, mental deficiency, and the 1927 Mental Deficiency Act. Issue 1 (March 2015) - Ruiz, Violeta
Highlights: The 1920s EL epidemic caused mental and behavioural disorders in children. By its legal definition, mental deficiency arose 'from birth or an early age'. Childhood victims of EL were therefore excluded from the Mental Deficiency Act. Clinicians linked the disorders to brain lesions, demanding achange in definition. The EL epidemic forced amendments to the original 1913 Mental Deficiency Act. Abstract : Encephalitis lethargica (EL) was an epidemic that spread throughout Europe and North America during the 1920s. Although it could affect both children and adults alike, there were a strange series of chronic symptoms that exclusively affected its younger victims: behavioural disorders which could include criminal propensities. In Britain, which had passed the Mental Deficiency Act in 1913, the concept of mental deficiency was well understood when EL appeared. However, EL defied some of the basic precepts of mental deficiency to such an extent that amendments were made to the Mental Deficiency Act in 1927. I examine how clinicians approached the sequelae of EL in children during the 1920s, and how their work and the social problem that these children posed eventually led to changes in the legal definition of mental deficiency. EL serves as an example of how diseases are not only framed by the society they emerge in, but can also help to frame and change existing concepts within that same society.